A Review of Combined Use of Biochar with Nitrogen Fertilizer as an Instrument for Improving Maize Yield and Soil Fertility - Kedir, Mohammed (Discoveries in Agriculture and Food Sciences, 2023)
The decline of soil fertility is one of the major problems around the world for producing crops and ensuring food security. Therefore, the review’s objective was to examine how biochar and inorganic nitrogen fertilizers affect soil physicochemical characteristics, as well as maize production and growth parameters. Similarly, biochar is a product of the thermochemical decomposition of biomass produced under limited oxygen. It has potential benefits in agriculture, such as improving soil fertility, water retention. The nutrient composition of biochar produced is determined by the type of feedstock used and the pyrolysis conditions. A study showed that adding biochar and nitrogen fertilizer decreased soil bulk density and enhanced water-holding capacity and soil chemical properties like pH, nitrogen, phosphorus, potassium, organic carbon, calcium, ECEC, and base saturation. Moreover, the review reported that the addition of N fertilizer and biochar greatly promoted crop N uptake and N content, which then increased leaf photosynthetic efficiency, dry matter accumulation, and grain yields. The findings discovered that when the rate of biochar and nitrogen increased, crop productivity and soil properties also increased significantly. It is concluded that applying biochar along with nitrogen fertilizer increased maize crop productivity as well as soil attributes more than applying biochar and nitrogen fertilizer separately. Therefore, farmers and agricultural experts should consider incorporating these practices into their land management strategies to improve overall agricultural sustainability.